Predatory Pricing in the Digital Platform Ecosystem: Challenges and Limitations of Indonesian Competition Law - I Wayan Partama Putra; A.A. Istri Eka Krisna Yanti; Anak Agung Sagung Ngurah Indradewi (CV. Tirta Pustaka Press, 2026)
The digital economy has transformed market structures through platform-based businesses. Aggressive pricing strategies, including subsidies and large discounts, may benefit consumers in the short term but can reduce competition by driving out small businesses and strengthening the dominance of large platforms. The digital economy relies on data and algorithms, making predatory pricing difficult to detect under conventional legal approaches. Therefore, this study examines its characteristics, identifies the limits of Indonesian competition law, and proposes a more adaptive legal approach. Moreover, Law No. 5 of 1999 does not specifically regulate algorithmic pricing, cross-subsidization, or data-driven market dominance, creating legal uncertainty in addressing predatory pricing in the digital economy. This study uses normative legal research with statutory and conceptual approaches. It examines laws on predatory pricing and analyzes the concepts of legal certainty, law enforcement, and distributive justice in competition law. This study employs normative legal research using statutory and conceptual approaches to analyze the adequacy of Indonesian competition law in addressing predatory pricing practices within digital platform markets. The findings show that current Indonesian competition law is insufficient to address below-cost pricing, algorithm-based pricing, and cross-subsidization practices used by dominant digital platform. Regulatory limitations, particularly in terms of evidence and supervision, result in suboptimal law enforcement. Furthermore, this situation demonstrates the failure to fulfill the principles of legal certainty, justice, and balance in business competition. Therefore, Indonesian competition law needs stronger digital market regulations, clearer rules for identifying predatory pricing, and greater institutional authority to supervise algorithm-driven business practices.